Biodegradable starch particles for controlled release applications: Swelling and leaching mechanisms. Issue 34 (25th January 2020) - Dias Maia, Juliana; Schmiele, Marcio; Ubbink, Job; Prata, Ana Silvia
Abstract: Starch‐extruded particles have only found infrequent use as delivery systems for active ingredients. We have previously shown that these particles are attractive for releasing hydrophobic compounds in water media. Here, we cover a range of amylose–amylopectin ratios and evaluate the presence of the thyme essential oil (TEO) as active compound to understand the dominant release mechanism in relation to the physicochemical properties of the starch matrices. Starch blends with high amylopectin content (1.8 and 15% amylose) could not be shaped into regular particles. For amylose contents higher than 28%, the equilibrium degree of swelling in water decreased with increasing amylose contents, from nearly 300% for an amylose content of 28–90% at an amylose content of 70%. For both lowest amylose contents, 1.8 and 15%, leaching of solids and disintegration of the particles resulted in a low apparent degree of swelling. The presence of TEO reduces the degree of swelling of the gelatinized starch matrix. This is explained by the formation of thymol–amylose complexes, which is confirmed by Fourier transform infrared spectroscopy analysis and X‐ray diffraction. Abstract :